2021
DOI: 10.1007/s41999-021-00549-6
|View full text |Cite
|
Sign up to set email alerts
|

Discordance and concordance on perception of quality care at end of life between older patients, caregivers and clinicians: a scoping review

Abstract: Aim The purpose of this review was to synthesise and critically analyse the points of discordance and concordance between consumers and clinicians about quality end-of-life care. Findings Respecting patient autonomy and the role of family is now clearly understood, but the role of healthcare provider and purpose of treatment withdrawal are still a matter of conflict between clinicians and patients or families. Clinician awareness of the possibility of misunderstanding by patients or families is the first step … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 63 publications
0
17
1
Order By: Relevance
“…A scoping review that included 21 qualitative studies revealed a mixture of concordance and discordance of perspectives between three parties: patients, professional care providers, and FCs. 5 Another narrative literature synthesis included 39 studies on EoLC to find factors contributing to concordance and discordance between family and patient EoLC preferences and decision-making. They found relational conflict and lack of awareness as contributing factors to discordance in EoLC preferences.…”
Section: Theoretical Framework and Methodological Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…A scoping review that included 21 qualitative studies revealed a mixture of concordance and discordance of perspectives between three parties: patients, professional care providers, and FCs. 5 Another narrative literature synthesis included 39 studies on EoLC to find factors contributing to concordance and discordance between family and patient EoLC preferences and decision-making. They found relational conflict and lack of awareness as contributing factors to discordance in EoLC preferences.…”
Section: Theoretical Framework and Methodological Approachesmentioning
confidence: 99%
“…[1][2][3][4] EoLC involves a multitude of functions, physical, spiritual, and psychosocial assessment, care, and treatment, delivered by health professionals and ancillary staff. 5 The team of healthcare professionals, who carried out these functions, include PC physicians, nurses, and social and spiritual care workers. Irrespective of ethnic background, family caregivers (FCs) get involved in every aspect of the PC journey and ethnic minority patients rely on more informal support from their families than from PC health professionals.…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors also demonstrated these characteristics can also be a source of ‘Autistic Advantage’ where concentrating for lengthy periods, attention to detail, and creative thinking are strengths in the work environment. In a further example, a scoping review conducted by Carlini et al (2021) on discordance and concordance on the perceptions of quality care at end of life between older patients, caregivers and clinicians found conflicts in the understanding between the parties. The authors note the conflict between consumers and healthcare professionals potentially hindered the value of care and may have an impact on trust in the health system to deliver care that meets patient expectations.…”
Section: Cpr Checklist For Market Research–integrative Literature Rev...mentioning
confidence: 99%
“… 20 Surrogates frequently prefer more aggressive cancer treatments and often have greater willingness to pay (WTP) to extend life than do patients. 10 , 21 , 22 , 23 We examined the stated EOL care preferences of Chinese patients with terminal cancer. This study aimed to provide empirical evidence for clinicians and surrogates on how to inform patients about a full set of preferences for EOL care, improve the quality of patient-centered care, and promote a favorable death for patients.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, physicians and surrogates operationalize care trade-offs without knowing the preferences of the patients with cancer, especially how much of their lifetime these patients would be willing to lose to attain their palliative care goals . Surrogates frequently prefer more aggressive cancer treatments and often have greater willingness to pay (WTP) to extend life than do patients . We examined the stated EOL care preferences of Chinese patients with terminal cancer.…”
Section: Introductionmentioning
confidence: 99%